Biotechnological techniques for intensification of protein extraction from the porcine pancreas - E. A. Kotenkova; A. G. Akhremko; E. K. Polishchuk; M. A. Aryuzina; M. E. Spirina (Теория и практика переработки мяса, 2022)
Processing of secondary products after slaughter of farm animals is in demand. The pancreas is a rich source of bioactive protein substances, effective extraction of which is a serious problem today due to their aggregation. The aim of the work was to assess the extractivity of protein substances of the porcine pancreas using sodium chloride, trehalose, arginine, and combination of glycine and proline. The protein concentration was determined in the obtained extracts by the biuret reaction and their protein composition was assessed by densitometry of two-dimensional electropherograms using software ImageMaster™ 2D Platinum powered by Melanie 8.0. The results showed a positive effect of anti-aggregation agents on the release of protein substances into a solution. The highest protein concentration (33.36±0.64 g/l) was observed when adding 1М L-arginine; however, it was conditioned mainly by an increase in the content of three major protein fractions rather than by diversity of the protein composition. In general, the use of 0.9% NaCl as an extractive agent was quite effective, but selectivity to certain protein groups was observed for anti-aggregation agents such as sodium chloride, trehalose, arginine, glycine and proline, as well as their combination. The obtained results are important for intensifying extraction of protein substances including target ones with the subsequent application in different fields.